Turkish Foreign Policy, 1774-2000. - Hale, William (Taylor and Francis, 2012)
Turkey and its predecessor state, the Ottoman Empire, have been at the centre of international relations for centuries. By the late eighteenth century, what had once been the dominant power in the eastern Mediterranean and south-east Europe was gradually falling apart. For the European statesmen of the nineteenth century, it had become the 'eastern question' - a complex problem of conflicts and alliances, which also raised difficult and sometimes insoluble questions for the Turks themselves. After the collapse of the empire at the end of the First World War, Turkey was reconstructed as a natio.